Mental health issues in Malaysia : a systematic review - Mohd Shahrul, Kamaruddin; Fatahyah, Yahya; Surena, Sabil; Aini Azeqa, Ma’rof; Maizatul Mardiana, Harun; Johari, Md Salim (National Association of Social Workers, 2022)
Mental health issues in Malaysia have been increasing especially during the novel coronavirus disease 2019 (COVID-19) pandemic which led to many researchers carried out in regard to the uprising mental health issues. As a result, this systematic review was conducted to identify the theme of the previous studies based on all information and materials gathered regarding mental health issues in Malaysia. The Systematic Literature Review (SLR) and Reporting Items for Systematic Reviews methodologies were used to perform this investigation. In light of this, literature searches were conducted to find articles and information on mental health in a number of indexed databases, including the Malaysian Journal of Science (MJS), Asian Journal of Psychiatry, Google Scholar, SCOPUS, ScienceDirect and Web of Science (WoS), between 2019 and 2022. Overall, this study shows four main themes, (1) the stage of community mental health, (2) factors that affect people's mental health, (3) mental health and action power and (4) efforts to deal with mental health issues. Therefore, the systematic review of this study provide useful information to the authorities which could lead to finding compatible solutions in dealing with mental health issues in Malaysia.